AeroStruct: Enable and Learn How to Integrate Flexibility in Design Contributions to the Closing Symposium of the German Research Initiative AeroStruct, October 13–14, 2015, Braunschweig, Germany /: Contributions to the Closing Symposium of the German Research Initiative AeroStruct, October 13–14, 2015, Braunschweig, Germany. (2018) - Unknown
No abstract available